Obesity and adiponectin - Scherer, Philipp (Henry Stewart Talks, 2009)
Adipose tissue as an endocrine organ, Local and systemic inflammation increases due to dysfunctional adipose tissue, Dysfunctional adipose tissue is more fibrotic, Factors involved in inflammation, Factors involved in energy homeostasis, The Adipokine panel for clinical studies, Impact of visceral fat pad on liver, Retinol binding protein 4 (RBP4), Resistin, Adiponectin, Adiponectin multimerization, Prospective marker of CVD, Hepatic insulin sensitizer, Anti-steatotic action of Adiponectin, A mediator of PPARg agonist action, Type 2 diabetic patients, Hypertension, Renal failure, Cancer, Transgenic overexpression of Adiponectin in ob/ob mice
Reviewed at 2015/11/24